The Implementation of Picture Series as Learning Media to Improve Students' Writing Ability Related to Historical Events in Recount Text - Gayatri, Devi Deti; Gaffar, Muhammad Andriana (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
The objectives of this research are: (1) to find out the class situation during the implementation of picture series in teaching writing, and (2) to determine the improvement of students' ability to write recount text using picture series. The research used a qualitative. The classroom action research design used in this research consisted of two cycles. The data were collected from observation, field notes, and interviews. The research participants are 34 students in the tenth grade of SMA YKM Tanjungsari. The results showed that picture series could improve students’ ability to write recount text, create a fun learning atmosphere, and increase students’ writing interest. In the first cycle, the percentage of learning activities was 18%; in the second cycle, 80% of students got excellent categories. The two cycles could effectively improve students' writing ability in recounting text. The students could develop their ideas to make a story and were active and enthusiastic in the teaching-learning process. It demonstrates that writing a recount text using picture series as learning media for X MIPA 1 student at SMA YKM Tanjungsari has been improved.